Meningkatkan Hasil Belajar Siswa Melalui Media Pembelajaran Audio Visual Pada Pelajaran Fiqih Kelas IX MTs Babussalam Besilam - As’ad Badar, Usmaidar, Khairunisa (Education Achievement: Journal of Science and Research, 2022)
Audio visual learning media is a variable that is used to improve learning outcomes in fiqh subjects, fardu kifayah material on corpses in class IX of MTs Babussalam Besilam. The subjects of this study were students of class IX MTs Babussalam Besilam, totaling 40 people. This research was conducted in two cycles, where each cycle consists of planning, acting, observing and reflecting. From the analysis of the data that the author got, it was known that the initial condition was that in class IX of MTs Babussalam Besilam there was a problem, namely student learning outcomes in fiqh subjects, fardu kifayah material on corpses that were low and far from the Minimum Completeness Criteria set by the Madrasah. In the pre-cycle implementation, the students' average score was 74.75 with 42.5% completeness. Then the first cycle was carried out, from the classroom action research data, there was an increase in the average value in the first cycle to 83.25 with a total completeness of 62.5%. Continued to the second cycle of action, in this action there was an increase again, namely the average score of 91.75 students with 90% completeness. This shows that the audio-visual learning media that the researchers used were able to improve learning outcomes in fiqh subjects, fardu kifayah material on corpses, although not 100%.